Optimal network topology for a locating system using RSSI-based direction finding - Nowak, Thorsten; Hartmann, Markus; Lindner, Thomas; Thielecke, Jörn (Indoor Positioning and Indoor Navigation (IPIN), 2015 International Conference on, 2015)
Location-awareness is one of the major challenges in wireless sensor networks (WSNs) today. Received signal strength indicator (RSSI)-based localization techniques are a promising approach to provide location information in WSNs utilizing low-cost hardware. In this paper, the performance of RSSI-based direction-of-arrival (DOA) is assessed. Therefore, the Cramér-Rao Lower Bound (CRLB) for direction estimation with RSSI measurements is derived in an analytical form. Furthermore, a position CRLB RSSI-based DOA estimates is presented. Since RSSI-based DOA is highly dependent on the direction of the received signal, and hence position estimates are, the network topology has a major impact on the feasible precision of the locating system. A methodology is shown to find the optimal WSN topology evaluating the position CRLB for RSSI-based DOA measurements.